Shapes and Colors Identification Used in Malvinas Camo and Sage Green Camo on the Field Service Uniforms (PDL) of the Indonesian National Army (TNI) - Andrian, Mohamad Reza; Hidayatullah, Taufan; Maulina, Rini (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Introduced during the 80th anniversary of the Indonesian National Armed Forces (TNI) on October 5th, 2025, the Sage Green camo pattern introduced as an update to the long-standing Malvinas pattern used since 1983. This study identifies the differences in pattern, shape, and color between these two camo designs. Data were collected through fabric sample observation and digital tracing, then analyzed using a comparative-descriptive method to determine their distinct visual characteristics. Observations indicate that Malvinas camo features a larger rapport size with 157 patterns. In contrary, Sage Green camo utilizes a smaller rapport with a higher density of 271 patterns. This disparity suggests that the Malvinas camo is optimized for silhouette disruption at long distances, while the dense Sage Green camo intended for better texture blending at closer range. The study concludes that the distinct geometric and color properties of these camos resulted in specialized tactical functions. These findings provide a foundational framework for developing future camo designs optimized to manipulate human visual perception.